PENGEMBANGAN RPP DAN LKPD MATEMATIKA DENGAN PENERAPAN PEMBELAJARAN BERDASARKAN MASALAH PADA MATERI PRISMA DAN LIMAS KELAS VIII SMP - Melva Yola Afdareza; Zuhri '; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is the restrict of mathematics learning instruments as supporting learning referring to 2013 Curriculum. This research aims to develop the RPP and LKPD of mathematics with the application of problem based learning on the subject matter of the prism and pyramid for the 8th grade students of SMP. Research development by Thiagarajan. Development is done through the following steps: (1) define; (2) design; (3) develop; and (4) disseminate. At the stage of define, the researcher conducted a needs analysis as first-end analysis, analysis characteristic of students, concept analysis, assignment analysis and learning aim specification. Furthermore gather the necessary materials to design RPP and LKPD. RPP and LKPD that had been developed then validated by 3 validator and revised based on advice from the validator. RPP and LKPD that has a valid then tested in the small group trial with subjects 10 students of class VIII-6 SMP Negeri 3 Tambang. Based on the analysis of data and discussion can be concluded that RPP and LKPD of mathematics with the application of problem based learning on the subject matter of the prism and pyramid for the 8th grade students of SMP to be valid by the average for the RPP is 3.74 and the average for LKPD is 3.44, and eligible practicalities to use students of class VIII.Keywords: RPP and LKPD of mathematics, Research and Development, Problem Based Learning, Prism and Pyramid